Evaluasi Kinerja Sistem Informasi Aplikasi Shopee Menggunakan Metode PIECES Framework - Putri Melinda; Joy Nashar Utama Jaya; Adi Hermawansyah (STMIK Budi Darma, 2022)
Currently, the competition for E-commerce platforms is getting tougher since the outbreak of the covid-19 pandemic, so many E-commerce companies are faced with various opportunities and threats both from within and from abroad. The use of the Shopee Application as an object of research is because Shopee is most accessed by young people where in 2021, according to the author, the Shoppe Application will experience a problem if it is used simultaneously when holding a big sale campaign. This study aims to measure the relationship between System Performance Evaluation using the PIECES framework method which includes 6 dimensions of performance, information, economics, control and security, efficiency, and service variables on Shopee's E-commerce Applications, which aims to determine the level of Application System Performance in terms of weaknesses, strengths and analyze what components need to be improved. This study uses the PIECES Framework method in analyzing data, the use of the PIECES framework method is very suitable in analyzing each system variable under study because it can provide real results on the effectiveness of the system used by the company. User satisfaction with mobile application-based services is measured by the PIECES framework to determine the level of user satisfaction with services. The results of research using the PIECES Framework resulted in an average score of 4.26 with a Likert scale. So service users are categorized as PUAS for the Shoppe application information system service